Pengaruh Model Value Clarification Technique (VCT) terhadap Penalaran Moral Siswa Kelas V Sekolah Dasar - Pratiwi, Dita Eriyanti; Sutarno; M. Imron Rosyadi (JKPD (Jurnal Kajian Pendidikan Dasar), 2024)
The purpose of this study was to determine the effect of the Value Clarification Technique model on the moral reasoning of fifth-grade elementary school students. The study was quantitative with a Quasi-Experimental Research approach and a Nonequivalent Control Group Design. The results showed an average pre-test score of 62.86 for the experimental class and an average post-test score of 81.67 for the experimental class. The average pre-test score of 62.86 for the control class and an average post-test score of 72.14 for the control class. The results of the t-test using an independent sample t-test showed a significance level (2-tailed) of 0.000 < 0.05, thus rejecting Ho.